Public Dementia Care in Terms of Equal Services - Family, Local and Multiethnic Perspectives, 2015 - Hamran, Torunn; Blix, Bodil Hansen (NSD - Norwegian Centre for Research Data, 2021)
Most people with dementia live at home, and relatives may be severely affected by the disease. Municipal health and care services aimed at both relatives and people with dementia have been established. It is necessary to ensure that the offers are perceived as relevant and are used. This is described as particularly important in areas with a Sami population. The purpose of the project was to gain knowledge about local and individual differences in the use and non-use of municipal health and care services, as well as explore practices to uncover and explain similarities and differences between municipalities, ethnic and social groups. The project is based on data from municipalities in northern Nordland, Troms and Finnmark. A questionnaire survey was conducted among relatives of people living at home with dementia in 32 municipalities, individual qualitative interviews with relatives of people living at home with dementia, focus groups with employees in municipal health and care services and focus groups with volunteers. The project is funded by the Research Council of Norway (HELSEVEL).